ChemInform Abstract: Enantiomerically Pure Compounds Related to Chiral Hydroxy Acids Derived from Renewable Resources. Issue 1 (3rd January 2013) - Haleema, Simimole; Sasi, Paleapadam Vavan; Ibnusaud, Ibrahim; Polavarapu, Prasad L.; Kagan, Henri B.
Abstract Review: 313 refs.